POLLUTION INDEX AND SEDIMENTATION RATE BASED ON LAND USE AT BANJIR KANAL BARAT AND SILANDAK RIVERS, SEMARANG - Ain, Churun; Rudiyanti, Siti; Dominig, Amryta; Adriani, Arina; Asih, Dilia Puspita (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2020)
Land use around the river, can affect the condition water quality of waters. The purpose of this study are to determine the pollution index and the rate of river sedimentation, and land use around the Banjir Kanal Barat and Silandak River. The method for sampling was purposive sampling. Sampling was carried out in the Banjir Kanal Barat and Silandak River, each of which had 5 points and 2 repetitions (P1 and P2). The variables analyzed were TSS, BOD, COD, total coliform where analyzed with Indonesian Standard National (SNI); DO, pH, temperature, discharge of water analyzed with Water Quality Checker (WQC), Buchanan method used to analyzed sedimentation rate, and sediment fraction. The results of the study, showed that IP in the Banjir Kanal Barat River obtained an IP value of 4.13 (lightly polluted), while the Silandak River obtained an IP value of 4.69 (lightly polluted). The highest sedimentation rate in the Banjir Kanal Barat River with a value of 35.64 tons / day, while the Silandak River has the highest value of 55.81 tons / day. Sediment fraction in Banjir Kanal Barat River is dominated by clay, and Silandak River it is dominated by clay. Land cover in Banjir Kanal Barat river are 3% industry, 85% settlement, 0% water and 12% vegetation, and Silandak River are 7% industry, 69% settlement, 5% water and 7% vegetation.